Pengembangan Media Video Animasi Pembelajaran Pendidikan Pancasila Berbasis Plotagon Studio dan Capcut Kelas II Sekolah Dasar - Puspitaningrum, Linda; Astutik, Leny Suryaning (Jompa Research and Development, 2025)
This research was motivated by the fact that teachers only used lecture methods during learning activities and had no access to engaging visual learning media. The aim of this study was to develop, validate, and assess the practicality of animated video media based on Plotagon studio and CapCut for the subject of Pancasila Education, focusing on the topic Symbols of Religious Diversity for Grade II students at SDI Raudlatul Musthofa. The research employed the ADDIE development model, which includes five stages: Analyze, Design, Develop, Implement, and Evaluate. The instruments used in this study included media expert validation sheets, material expert validation sheets, and questionnaires for teacher and student responses. The results showed that Media Expert 1 gave a validity score of 95.4% (